Highly Chemo‐ and Stereoselective Catalyst‐Controlled Allylic C−H Insertion and Cyclopropanation Using Donor/Donor Carbenes - Zhu, Dong; Chen, Lianfen; Zhang, He; Ma, Zhiqiang; Jiang, Huanfeng; Zhu, Shifa (Angewandte Chemie International Edition, 2018)
The highly chemo‐, enantio‐, and diastereoselective catalyst‐controlled intramolecular allylic C−H insertion and cyclopropanation of donor/donor carbenes are reported. The RuII/Pybox complex selectively catalyzed the intramolecular allylic C−H insertion, providing vinyl‐substituted dihydroindoles with greater than 20:1 chemoselectivity and up to greater than 99 % ee. Chiral dirhodium(II) tetracarboxylates, however, selectively promoted the intramolecular cyclopropanation, giving rise to cyclopropane‐fused tetrahydroquinoline derivatives in excellent yields with greater than 99:1 chemoselectivity and up to 97 % ee. Rh versus Ru: The highly chemo‐, enantio‐ and diastereoselective catalyst‐controlled intramolecular allylic C−H insertion and cyclopropanation of donor/donor carbenes is reported. The RuII/Pybox complex selectively catalyzes the intramolecular allylic C−H insertion, providing vinyl‐substituted dihydroindoles. Chiral dirhodium(II) tetracarboxylates, however, selectively catalyzed the intramolecular cyclopropanation.